Colaboração interprofissional no projeto Saúde e prevenção nas escolas: o caso de Sobral/CE - Vieira, Francisca Maria Bezerra Ribeiro (2013)
Our daily work is permeated by constant social relations that occur in work organizations, so the interprofessional collaboration constitutes a topic of great significance in the context of these organizations, in order to meet the needs in teamwork, especially in the form of services health care. Studying interprofessional collaboration in Health and Prevention in Schools (PSPE) is relevant for the potential to analyze it in a project, whose principle intersectorality, signaling the evidence of strengths and weaknesses in the relationship between the professionals involved in this proposal; beyond the possibilities of strengthening the theoretical and conceptual model for interprofessional collaboration and enrich the scientific literature on this subject relevant to the achievement of best practice in health. This study aimed to examine to what extent occurs in interprofessional collaboration PSPE the city of Sobral - CE. This is a case study with a qualitative approach. At the stage of data collection examined documents relating to the Health and Prevention in Schools and applied questionnaires to key subjects. The theoretical and methodological Interprofessional Collaboration Model D'Amour (1997) supported the data analysis. For the four dimensions and the ten indicators, the results showed that: the articulators of reach PSPE partially successful in conducting its activities to work together around common goals; PSPE professionals guide their behavior according to their professional interests and not according to the interests of teenagers and young people are few opportunities for members of the Project to meet and interact with each other, there is a perceived competence and confidence in the ability of others to take responsibility; formal agreements occurring within the Project not are consensual and are still under negotiation or construction, the infrastructure for the exchange of information is not used properly and / or is incomplete, the role of public spheres is not adequately promoting the implementation of structures for the development of actions taken within the PSPE; existing leadership in the Project is the type fragmented and somewhat shocking, there are moments of training for professional members of PSPE, however, subjects reveal that the articulators responsible for these moments are not always well prepared to perform them, the spaces and moments of meeting professionals are PSPE to discuss specific issues and specific, that do not address contextual issues as a whole. These results indicate that the level of interprofessional collaboration developed in this project is kind of collaboration "in development", to which D'Amour et al. (2008) constitutes the collaboration that is not stuck with the roots in the cultures of the organizations and may still be subject to revaluation based internal or environmental factors. It is observed in this study that the performance at maximum (active) interprofessional collaboration within this project is something possible, however, remains a challenge to be conquered. You must enter the action agenda of managers and professionals involved in the context of PSPE, conceptual aspects and practice of collaboration for the improvement of living conditions of adolescents and youth of our society.